POLITIK HUKUM PENGATURAN RADIO REPUBLIK INDONESIA BERDASARKAN PERATURAN PERUNDANG-UNDANGAN TENTANG PENYIARAN DI INDONESIA - NIM. A1011211016, DIAH IKA SAFITRI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This research is entitled Legal Politics of Radio Regulation of the Republic of Indonesia Based on Laws and Regulations on Broadcasting in Indonesia. The problem in this study is how to Regulate the Position of Radio of the Republic of Indonesia based on the Broadcasting Laws and Regulations in Indonesia and the impact of the Current Position Arrangement of Radio of the Republic of Indonesia. This study aims to analyze in depth the direction in the position of broadcasting regulation and policy as well as the impact of regulating the position of broadcasting as a Broadcasting Institution that has undergone transformation from a Government Broadcasting Institution to a Public Broadcasting Institution and analyze the impact of changes in the regulation of the position of Radio the Republic of Indonesia as a broadcasting institution and provide recommendations for the ideal position of public broadcasting in Indonesia. The research methods used are normative sociological legal research with a qualitative descriptive approach, a conceptual approach, and a legislative approach. Data obtained through literature studies, interviews and document studies as supporting data The results of the research show that the Legal Politics in Law Number 24 of 1997 concerning Broadcasting as a government broadcasting institution, namely even though it was formed in a one-way or central nature, in the formulation to its implementation is optimal. Then, the legal politics in Law Number 32 of 2002 concerning Broadcasting as a public broadcasting institution in its formulation is good, but in its implementation it does not run according to what has been formulated. This has an impact on institutions, budgets and staffing. The legal politics in the existing Broadcasting Law should be two-way, so that it can benefit all stakeholders in public broadcasting, including broadcasting operators, the public, the government and the House of Representatives. This makes Radio Republik Indonesia able to have the opportunity to continue to exist by using various technological advances. Law Number 6 of 2023 on Job Creation with an equal status. However, within it, the form of broadcasting is unidirectional where the government's role is more dominant, which can trigger centralization again and the regulation of migration from analog to digital that is still under debate. Keywords: Public Broadcasting Institution, Radio Republik Indonesia, Legal Politics Abstrak Penelitian ini berjudul Politik Hukum Pengaturan Radio Republik Indonesia Berdasarkan Peraturan Perundang-Undangan Tentang Penyiaran Di Indonesia. Permasalahan dalam penelitian ini adalah bagaimana Pengaturan Kedudukan Radio Republik Indonesia berdasarkan pada Peraturan Perundang-Undangan Penyiaran di Indonesia dan dampak Pengaturan Kedudukan Radio Republik Indonesia Saat ini. Penelitian ini bertujuan untuk menganalisis secara mendalam arah dalam kedudukan pengaturan dan kebijakan penyiaran serta dampak pengaturan kedudukan penyiaran sebagai Lembaga Penyiaran yang mengalami transformasi dari Lembaga Penyiaran Pemerintah menjadi Lembaga Penyiaran Publik serta menganalisis dampak perubahan pengaturan kedudukan Radio Republik Indonesia sebagai lembaga penyiaran serta memberikan rekomendasi ideal kedudukan penyiaran publik di Indonesia. Metode penelitian yang digunakan adalah penelitian hukum normatif sosiologis dengan pendekatan deskriptif kualitatif, pendekatan konseptual, dan pendekatan Perundang-Undangan. Data yang diperoleh melalui studi Pustaka, wawancara dan studi dokumen sebagai data pendukung Hasil penelitian menunjukkan bahwa Politik Hukum pada Undang-Undang Nomor 24 Tahun 1997 tentang Penyiaran sebagai lembaga penyiaran pemerintah yaitu meskipun dibentuk bersifat searah atau sentral namun dalam dari perumusan hingga implementasinya sudah optimal. Kemudian, politik hukum pada Undang-Undang Nomor 32 Tahun 2002 tentang Penyiaran sebagai lembaga penyiaran publik dalam perumusannya sudah baik, namun pada implementasinya tidak berjalan sesuai dengan yang sudah dirumuskan. Hal ini berdampak pada kelembagaan, anggaran dan kepegawaian. Politik hukum pada Undang-Undang Penyiaran yang ada seharusnya bersifat dua arah, sehingga dapat menguntungkan semua pemangku kepentingan yang ada di penyiaran publik termasuk bagi penyelenggara penyiaran, masyarakat, pemerintah dan Dewan Perwakilan Rakyat. Hal ini menjadikan Radio Republik Indonesia dapat memiliki kesempatan untuk tetap eksis dengan menggunakan berbagai kemajuan teknologi. Undang-Undang Nomor 6 Tahun 2023 tentang Ciptakerja dengan kedudukan yang sama. Namun, didalamnya bentuk penyiaran bersifat searah yang mana peran pemerintah lebih dominan sehingga dapat memicu sentralistik kembali serta pengaturan migrasi dari analog ke digital yang masih ada perdebatan. Kata Kunci: Lembaga Penyiaran Publik, Radio Republik Indonesia, Politik Hukum